Negros do trilho e as perspectivas educacionais - Ribeiro, Rosa Maria Barros (1995)
The aim of this work is to analyze afro-Brazilian people expenences and representations about school, school constructions and representations about afro-Brazilian people, ethnical relationships in school and educational contents transmission process of ethnical topics. The research, that analyze systematically a specific reality of the Brazilian context, have been realized with black families of Trilho community by no-directed interviews and focuses on fundamental aspects of their lives like living conditions, work, education, black identity and on their perceptions about the central theme of the study. The study have been realized in the light of bibliographic sources and of studies realized by «afro descendants» teachers about education, «social whitening» in Brazil and social, economic and cultural depreciation and exclusion of black community members. These studies, that are no based on an ethnocentric thought that reject knowledge from other ethnical groups, aims recover afro-Brazilian cultural aspects and initiate a debate about Brazilian multiculturalism and different kinds of knowledge. Our study prove that racism is present in school, by discourse, didactic manuais and interpersonal relationships. It straightens exclusion process that marginalize black people of Trilho community. We conclude toa that process of construction of black identities doesn't start in school, but in other social spaces. The study identify a systematic ideological construction process that denies black presence in Ceara State and a consequent racist attitude. The study concludes that school reality in Ceara and in other Brazilian states is similar. The school promote a pedagogy of silence and resume the study about black community on May 13 celebrations and on slavery period and abolition. The participation of black people in the construction of national culture is reduced to inexpressive levels. The school, that would be a place where ali social and ethnical groups citizenship is constructed, becomes an instrument apparently neuter, where there is no place for ethnic studies and discussions. In this sense, school does not contribute to the democratization of the Brazilian society and assists to the maintenance of social, politic and economic status quo. The study concludes also that school is not able to face up to the question of ethnic relationships.